Basic Concepts of English Syntax: Structure, Patterns, and Common Issues in English Writing - Tarigan, Zulayha Ulinta; Kinanti, Kinanti; Hanum, Atika; Kholijah, Siti; Ismahani, Siti (MUDABBIR Journal Research and Education Studies, 2025)
Syntax is a core component of linguistic knowledge that plays a crucial role in the construction of meaningful sentences. In English, syntactic rules determine how words are organized into phrases, clauses, and sentences to convey clear and accurate meaning, particularly in written communication. This article discusses the basic concepts of English syntax by outlining its definition, fundamental elements, sentence structures, and practical use in writing. In addition, common syntactic problems frequently encountered by English learners are examined along with their theoretical causes. The article is intended as a conceptual and pedagogical overview rather than a research report, aiming to support students and general readers in developing a clearer understanding of English sentence structure and improving writing quality through appropriate syntactic use.